Comparative study of effects of different positions of limbs on blood pressure of hypertensive patients - M Shaban; Z Parsa-yekta; A Mehran; N Soltani mollayaghobi (Tehran University of Medical Sciences, 2004)
Introduction: In hypertensive patients M position (sitting, right arm at the level of heart and both plantar surface of foots on the floor) is the standard position for measurment of blood pressure since it reveals the "true" pressure. Materials and Methods: It is a quaziexperimental study that compares effect of different positions of limbs on blood pressure of hypertensive patients. The sample size was consisted of 100 hypertensive patients. A questionnaire and a check list for systolic and diastolic blood pressure of the patients in different positions were used. One researcher collected all of the data. At first demographic data, weight and hight were recorded. After 5 minutes in sitting position in 3 different comparing positions, M (sitting, right arm at the level of heart and both plantar surface of foots on the floor), A (sitting, right arm hanging beside the body and both plantar surface of foots on the floor) and B (sitting, right arm hanging beside the body and right foot on the left knee), blood pressure was measured and recorded. The study methods included interview and physiologic measurement. The paired t-test for related measure was applied in order to analyse the data. Results: The results showed that the difference of mean systolic and diastolic blood pressure in "A & M", "B & M" and "B & A" positions was significant (paired t test, p<0.0001) and the mean of systolic and diastolic blood pressure in "A" position was more than "M" position, "B" position was more than "M" position and "B" position was more than "A" position. Conclusion: According to the findings of this study, "B" position has the greatest effect and "M" position has the lowest effect on increasing the systolic and diastolic blood pressure. This research indicated that attention to the limbs position during the measurement of blood pressure is very important.